Disability hate crime: perspectives for change - Burch, Leah; Wilkin, David (Routledge studies in crime and society, 2025)
"Bringing together perspectives from academics, practitioners, campaigners, and activists, this book explores the victimology of disability hate crime (DHC). For the first time, this book brings together recent academic thought, the stance of those working for the United Nations to further the rights of disabled people, and a helpful toolkit of how to advance the status of the disabled victim of hate crime. Campaigners, support workers and legal scholars present a tangential approach to revealing the plight of disabled victims, and their associates. The book will reveal the expertise required to understand experiences of victimisation and how to help reconstruct the lives of those affected by this type of violence. Never before has a book produced such a nuanced and multidisciplinary approach to discussing disability hate crime. This volume will be useful, not only for those academically interested in how disability hate crime is perpetrated, but also for scholars who wish to study how to raise awareness and lobby for change. It is essential reading for those engaged with hate studies, victimology, disability, and vulnerable communities, as well as practitioners and campaigners"--